Analysis of Financial Distress and Bankruptcy Using the Altman Z-Score Method on the Indonesia Stock Exchange (IDX) in 2020 - 2022 - Irwanto, M. Endrik; Rodoni, Ahmad; Riniawati, Rina (Training & Research Institute - Jeramba Ilmu Sukses (TRI-JIS), 2024)
This research analyzes financial distress and bankruptcy using the Altman Z-Score method and its influence on share prices in construction service companies listed on the Indonesia Stock Exchange (IDX) for 2020 - 2022. The variables tested in this research consist of working capital to total assets, retained earnings to total assets, earnings before interest and tax to total assets, market value of equity to book value of debt, sales to total assets as independent variables, and share prices as dependent variables. The population in this research is construction services companies listed on the Indonesia Stock Exchange for 2020 - 2022. The sampling technique used in this research is purposive sampling, and a sample of 63 data from 21 construction services companies listed on the Indonesia Stock Exchange in 2020-2022 that meet specific criteria was obtained. The data analysis technique used in the research is panel data regression analysis and classical assumption testing using EViews version 13 statistical software. This research shows that in 2020, 18 construction service companies were in the distress zone and 3 companies were in the gray zone. In 2021, 17 construction service companies will be in the distress zone and 4 in the gray zone. In 2022, 17 construction service companies will be in the distress zone and 4 in the gray zone. The earnings before interest and tax to total assets have a significant effect and positive relationship with share prices. Working capital to total assets, retained earnings to total assets market value of equity to book value of debt, and sales to total assets do not have a significant effect and have a negative relationship to stock prices.